2020
DOI: 10.1186/s13148-020-00831-7
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of constitutional DNA methylation in familial melanoma

Abstract: Background: Heritable epigenetic alterations have been proposed as an explanation for familial clustering of melanoma. Here we performed genome-wide DNA methylation analysis on affected family members not carrying pathogenic variants in established melanoma susceptibility genes, compared with healthy volunteers. Results: All melanoma susceptibility genes showed the absence of epimutations in familial melanoma patients, and no loss of imprinting was detected. Unbiased genome-wide DNA methylation analysis reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Limitations of this study include J o u r n a l P r e -p r o o f the small number of families studied, and any causative epimutation may occur in a subset of melanoma families (and unlikely to be common in all). In addition, samples were interrogated on a 450K Illumina array that interrogated methylation status of CpG sites in all gene promoters but that did not cover other possible regulatory sequences (Salgado et al 2020). Future research focused on additional epigenetic mechanisms, including non-coding RNA, will continue to help elucidate unexplained predisposition to hereditary melanoma.…”
Section: Multi-omics Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Limitations of this study include J o u r n a l P r e -p r o o f the small number of families studied, and any causative epimutation may occur in a subset of melanoma families (and unlikely to be common in all). In addition, samples were interrogated on a 450K Illumina array that interrogated methylation status of CpG sites in all gene promoters but that did not cover other possible regulatory sequences (Salgado et al 2020). Future research focused on additional epigenetic mechanisms, including non-coding RNA, will continue to help elucidate unexplained predisposition to hereditary melanoma.…”
Section: Multi-omics Approachesmentioning
confidence: 99%
“…A more recent report analyzed five Dutch families, with at least three melanoma cases in different generations, for associated DNA methylation alterations. The authors concluded that despite several clustered epimutations discovered, these candidates were unlikely driving the predisposition ( Salgado et al., 2020 ). Limitations of this study include the small number of families studied, and any causative epimutation may occur in a subset of melanoma families (and unlikely to be common in all).…”
Section: Future Perspectivesmentioning
confidence: 99%